Serum Heparin-Binding Protein as a Potential Biomarker to Distinguish Adult-Onset Still’s Disease From Sepsis - Tian, Rui; Chen, Xia; Yang, Chengde; Teng, Jialin; Qu, Hongping; Liu, Hong-Lei (Frontiers in Immunology, 2021)
Adult-onset Still’s disease (AOSD) is a systemic, multifactorial, autoinflammatory disease for which the etiopathogenesis is not well understood. Given the similarities in clinical and laboratory features between this disease and sepsis, and the differences in treatment strategies for these two diseases, specific diagnostic markers are crucial for the correct diagnosis and management of AOSD. Previous studies have shown plasma heparin-binding protein (HBP) is a promising potential biomarker for AOSD; thus, this study aimed to detect serum HBP levels in patients with AOSD or sepsis to assess its potential as a biomarker for differential diagnosis. We found that serum HBP levels were significantly higher in people with active AOSD than that in those with inactive AOSD. People with sepsis had higher serum HBP levels compared with those who had active or inactive AOSD. We calculated the area under the receiver operating characteristic (ROC) curve to assess whether HBP could be used to differentiate active from inactive AOSD; this was 0.811 with sensitivity 0.650, specificity 0.811, and cutoff HBP value of 35.59 ng/ml. The area under the ROC curve for HBP as a biomarker to differentiate AOSD from sepsis was 0.653, with sensitivity 0.759, and specificity 0.552, and cutoff HBP value of 65.1 ng/ml. Taken together, the results of our study suggest that serum HBP could be a useful diagnostic biomarker to evaluate disease activity in people with AOSD, and to differentiate AOSD from sepsis.